Application of waste treatment sludge from water treatment in brick production - Ainul Haezah Noruzman; Norhayati Palil; Rosnani Ahmad; Khairul Salleh Baharudin (International Journal of Technology, Innovation and Humanities, 2020)
The aim of the study is to investigate the potential use of water treatment sludge in brick properties as building material. The sludge was collected from water treatment plant and the percentages used in the mixes were 3%, 5%, 7%, 10% 15%, 20%, 40%, and 60% by weight of sand in brick. The specimen without sludge was prepared for comparison. The testing involved chemical analysis of sludges using energy dispersive X-ray fluorescence (ED-XRF) technique. Testing of compressive strength was done for hardened state properties. The samples were cured at 7 and 28 days, and the average of three samples of brick samples was measured. The results revealed that the waste sludges had higher components of Zn, Cu, Pb, and As, which was trace element concentrations in the dry sludge samples. Comparisons in terms of strength were made from the control and brick containing sludge specimens. It was observed that sludge in brick performed better when mixed with 5% as partial replacement of sand. However, the more the addition of percentages of sludge in brick, the lesser the strength observed. It can be concluded that waste treatment sludge as a result from the process of water treatment can be utilized as partial replacement of sand in brick production.